Association of lower extremity injuries and injury mechanism with previous concussion history in adolescent athletes. (March 2021) - Biese, Kevin M.; Stamm, Julie M.; Wichman, Daniel M.; Hetzel, Scott J.; Post, Eric G.; Bell, David R.
Abstract: Objective: Determine the association between concussion and subsequent contact, non-contact, and overuse lower extremity (LE) injuries in a cohort of adolescent athletes. Secondarily, to identify this association between males and females. Study design: Cross-sectional. Setting: Summer athletic events with participants ages 12–18. Main outcome: Anonymous survey included sport-related injuries (injury month/year) and participants classified injuries as a contact, non-contact, overuse injury, or concussion. Multivariable logistic regression analyses were used to examine associations between a concussion event and a subsequent LE injury while controlling for age and any previous LE injury. Results: A concussion was reported in 219 athletes (Female = 96, 44%) and were matched with 219 non-concussed athletes (438 total participants). Concussion was not association with a specific injury mechanism but was significant for any subsequent LE injury (OR = 1.58 95%CI = [1.03–2.41]; p < 0.05). Concussed females were more likely to report any subsequent LE injury compared to non-concussed female athletes (2.49[1.31, 4.74]; p < 0.01). This relationship was not observed between concussed and non-concussed males (1.11[0.62–1.99]; p > 0.5). Conclusion: A history of concussion was associated with any subsequent LE injury, but not associated with a specific mechanism of injury. The association with concussion and a subsequent LE injury was different between males and females. Highlights: Concussion is associated with subsequent lower extremity injury. Concussion was not associated with a specific lower extremity injury mechanism. Concussion's association with subsequent lower extremity injuries was significant in females. Concussion's association with subsequent lower extremity injuries was not significant in males.